A busca da competitividade pela formação de rede de empresas: um estudo na Central Mais Supermercados - Ribeiro, Claudete Fogliato; Baisch, Lindiane da Veiga; Camfield, Luis Henrique Ramos (Revista Gestão da Produção Operações e Sistemas, 2006)
The establishment of a company network represents an important business strategy to promote developmentand competitive advantages. The economy globalization and its effects, mainly related to the technologyadvances and the stimulating competition, force the companies towards the search for innovations and newadministrative methods. It is believed that such study is relevant, because of its recency thus requiring adeeper knowledge by the academic and business areas. This paper attempted to present in-depth theoreticalknowledge through a critical analysis, diagnosing the businessmens perception regarding the achived resultsafter integrating a company network. As a study method, an exploratory research was utilized, consisting ofbibliographical and field survey. This study also allowed for the identification and analysis on the mainadvantages, customers satisfaction and dissatisfaction along with the development of the operational activitiesof Central Mais Supermarket, located in the city of Santa Maria, Brazil. The paper highlights the importanceof the establishment of the Company Network as a competitive, surviving and alternative strategy, so that thesupermarket business can operate in the economic and social aspects, reducing its costs and offering qualityservices and products, reaching more new customers.Keywords: Company Network; Competitiveness; Strategy.